Respuesta :
This is what I had figured out.
27^(2/3) = [cube root (27)]^2 = 3^2 = 9
The final answer to the expression is 9.
27^(2/3) = [cube root (27)]^2 = 3^2 = 9
The final answer to the expression is 9.
Answer: The radical equivalent of [tex]27^{\frac{2}{3}[/tex] = 9.
Step-by-step explanation:
Since we have given that
[tex]27^{\frac{2}{3}[/tex]
We need to find the radical equivalent to it
We will use the "exponential law" .
[tex](a^m)^\frac{1}{n}=a^{\frac{m}{n}}[/tex]
So, it becomes,
[tex][(27)^\frac{1}{3}]^2\\\\=[(3^3)^{\frac{1}{3}}]^2\\\\=[3^\frac{3}{3}]^2\\\\=3^2\\\\=9[/tex]
Hence, the radical equivalent of [tex]27^{\frac{2}{3}[/tex] = 9.